Shared Genetic Etiology for Migraine and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Shared loci for migraine and epilepsy were found on chromosomes 14q12-q23 and 12q24.2-q24.3 in a linkage analysis study of a Finish family with a complex phenotype, in a report from Folkhalsan Institute and other centers in Helsinki and Oulu, Finland; University of California, Los Angeles; and Wellcome Trust Sanger Institute, Cambridge, UK.